Electrical and optical properties of nitrogen doped SnO2 thin films deposited on flexible substrates by magnetron sputtering. (August 2015) - Fang, Feng; Zhang, Yeyu; Wu, Xiaoqin; Shao, Qiyue; Xie, Zonghan
Graphical abstract: The best SnO2 :N TCO film: about 80% transmittance and 9.1 × 10 −4  Ω cm. Highlights: Nitrogen-doped tin oxide film was deposited on PET by RF-magnetron sputtering. Effects of oxygen partial pressure on the properties of thin films were investigated. For SnO2 :N film, visible light transmittance was 80% and electrical resistivity was 9.1 × 10 −4  Ω cm. Abstract: Nitrogen-doped tin oxide (SnO2 :N) thin films were deposited on flexible polyethylene terephthalate (PET) substrates at room temperature by RF-magnetron sputtering. Effects of oxygen partial pressure (0–4%) on electrical and optical properties of thin films were investigated. Experimental results showed that SnO2 :N films were amorphous state, and O/Sn ratios of SnO2 :N films were deviated from the standard stoichiometry 2:1. Optical band gap of SnO2 :N films increased from approximately 3.10 eV to 3.42 eV as oxygen partial pressure increased from 0% to 4%. For SnO2 :N thin films deposited on PET, transmittance was about 80% in the visible light region. The best transparent conductive oxide (TCO) deposited on flexible PET substrates was SnO2 :N thin films preparing at 2% oxygen partial pressure, the transmittance was about 80% and electrical conductivity was about 9.1 × 10 −4  Ω cm.